The power of context in language teaching and learning - Frodesen, Jan (Thomson Heinle, 2005)
THE POWER OF CONTEXT IN LANGUAGE TEACHING AND LEARNING provides a highly accessible, in-depth study of the relationship between discourse and the context of language teaching and learning. A tribute to Marianne Celce-Murcia's groundbreaking and distinguished work, this text contains a strong combination of theory and practice that will benefit any language teacher or student.